Anthropology of the City: A Social Viewpoint, Main Tendencies, Perspectives and National Traditions of Research.: An example of Czech Urban Anthropology - Soukupová, Blanka (Lidé města, 2010)
The text presents a brief outline of the development of Czech urban anthropology from its beginning in the 1950s until the present. It follows the viewpoints of this highly promising discipline and its individual stages of development. It focuses particular attention on the situation after 1989. While in the first decade after the Velvet Revolution research on multiethnicity and multiculturality in the city prevailed, today anthropologists have proceeded to try to explain the city as a whole. At the same time the text illustrates how the birth of urban anthropology was related to a change in the understanding of the key concept of Czech ethnography – folk – and to a change of point of view of researches on the city. From the ’50s until the ’80s the proletariat was regarded for ideological reasons as the core of urbanized space; urban anthropology thus coincided with workers’ ethnography.